Pemanfaatan Daun Sirsak Sebagai Masker Peel Off Untuk Mengurangi Jerawat - Nurulisma Saputri; Raya Wida Nur Vivid (Garina, 2022)
Soursop leaves contain steroid or terpenoid compounds, flavonoids, coumarins, alkaloids, and tannins. The flavonoid compounds in soursop leaves work as antioxidants. The purpose of this study was to find out how to make Peel Off face masks from soursop leaves, to find out the benefits of Peel Off facial masks from soursop leaves on facial skin calls, to determine public acceptance of Peel Off facial masks products from soursop leaves to reduce acne. The researcher used the observation method, the interview method, the experimental method, the documentation method, the R&D method, and the questionnaire method. Peel Off mask product from soursop leaves has a composition of soursop leaf extract 3gr, Natrosol 5gr, Propylene Glycol 6ml, Propyl paraben 1gr, Methyl paraben 1gr, Sodium Lauryl Sulfate 2gr, distilled water 6ml distilled water, 9ml polyvinyl alcohol. From the results of public trials to the public, the products made are effective in reducing whitehead acne, acne in the T zone, acne papules, acne fulminans, acne menchanica, and can brighten the face. The results of the calculation of public acceptance of the Peel Off facial mask product from soursop leaves of the fifth experiment have an average color result of 3.5. Thickness 3.5. Texture 3.6. Scent 3.4. Side effects 3.5. This Peel Off face mask from soursop leaves is suitable for use on the face because it contains antibacterial and antioxidant properties that are very effective in reducing acne.